Factors-Factors Affecting Tax Avoidance - Lestari, Ayu; Dewi, R. Rosiyana; Wahyuni, Ika; Windiyani, Windiyani (Green Publisher Indonesia, 2023)
This study aims to analyze and prove empirically (1) the effect of executive character on Tax Avoidance, (2) the effect of thin capitalization on Tax Avoidance and (3) the effect of the book tax gap on Tax Avoidance. This research method is carried out by taking secondary data, namely manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 2020. The data collection technique uses the purposive sampling method and the method used in analyzing is the multiple regression analysis method. The results show that the executive character and thin capitalization have a positive effect on tax avoidance. while the book tax gap has a negatif influence on tax avoidanc. So the H3 in this study was rejected. Based on the results of the partial test, the research shows that the effect of the book tax gap on tax avoidance is a negative effect, which means that the larger the book tax gap in the company, the no indication of an increase in tax avoidance